MEDICAL RECORD SYSTEM DI PUSKESMAS BERBASIS WEB - Laupode, Moh Afrianto; Dai, Roviana H; Zakaria, Alfian (Diffusion: Journal of Systems and Information Technology, 2022)
This present study is motivated by a problem experienced by supervisors in processing data where they remain applying Microsoft Excel so that it is eventually time-consuming and leading to frequent data duplication. In addition, the data storage process is still in the form of document or archive thus, it delays the search process over certain data, and it is vulnerable to be lost or corrupted. The study is classified as a descriptive study which uses prototype method for system development. The study's result is a Web-based Regional Asset Inventory Information System which is helpful in the regional asset inventory process. Additionally, the system can help prepare and register data so that it benefits Bone Bolango District administration in relation to the regional asset inventory process.  Keywords: Asset Inventory, Regional Asset Inventory Information System of Bone Bolango District, Prototype